Do losses trigger deliberative reasoning? - Jeffrey Carpenter; David Munro (Judgment and Decision Making)
There is a large literature evaluating the dual process model of cognition, including the biases and heuristics it implies. However, our understanding of what causes effortful thinking remains incomplete. To advance this literature, we focus on what triggers decision-makers to switch from the intuitive process (System 1) to the more deliberative process (System 2). We examine how the framing of incentives (gains versus losses) influences decision processing. To evaluate this, we design experiments based on a task developed to distinguish between intuitive and deliberative thinking. Replicating previous research, we find that losses elicit more cognitive effort. Most importantly, we also find that losses differentially reduce the incidence of intuitive answers, consistent with triggering a shift between these modes of cognition. We find substantial heterogeneity in these effects, with young men being much more responsive to the loss framing. To complement these findings, we provide robustness tests of our results using aggregated data, the imposition of a constraint to hinder the activation of System 2, and an analysis of incorrect, but unintuitive, answers to inform hybrid models of choice.